Implementation of MVC Architecture in a Web-based Mail Management System (E-Archive) - Setiadi, Ade; Alfiah, Fifit; Ardiansah, Teddy; Bin Ladjamudin, Al Bahra; Haryanto, Haryanto (Journal Sensi: Strategic of Education in Information System, 2024)
Companies, business entities, and institutions—both private and government—need archival activities because they are very important. To do it well requires improvement and refinement to achieve goals. All organizations, both government and private, must have complete and accurate data and information, knowing how important archiving is to assist leaders in making decisions or dealing with problems at the Larangan District Office, Tangerang City. Especially in the general section, archiving and document activity processes are still conventional, so it take a long time to complete. Because data is spread across many places and uses many formats, the process of selecting and reporting data is difficult to process well. This web-based electronic archiving system will be created using the Laravel framework and implementing the MVC(Model-View-Controller) architecture as a powerful and widely used software design pattern that encourages separation of concerns, code reuse, and maintainability enabling the archiving of incoming mail and mail. out serves as a data storage location. Therefore, the new e-archive system is expected to reduce errors when processing data, make the search process faster, and make reports that are in accordance with existing data.